1975
DOI: 10.1139/v75-163
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Proton Transfer Reactions of Carbon Acids. V. Variation of Primary Deuterium Isotope Effect with Solvent Composition for the Reaction of Di-(4-nitrophenyl)methane with t-Butoxide in t- Butyl Alcohol–Toluene Mixtures

Abstract: ARNOLD JARCZEWSKI, PRZEMYSLAW PRUSZYNSKI, and KENNETH T. LEFFEK. Can. J. Chem. 53, 1176 (1975).The second-order rate constants, activation parameters, and primary deuterium isotope effects are reported for the proton transfer reaction from di-(4-nitropheny1)methane to t-butoxide ion in a series of solvents containing varying amounts of toluene in t-butyl alcohol. Increasing toluene content in the solvent decreases the rate constant and increases the enthalpy of activation, while the entropy of activation becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1975
1975
2001
2001

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…That both the formation and decomposition reactions should have negative entropies of activation would not have been predicted, since the latter would be expected to be much more positive, within the experimental error. However, negative entropies have been observed for other reactions (14,18 that the incipient chloride ion enhances the acid, the negative entropies are again consistent solvation of the transition state of the decom-with many reports in the literature (19)(20)(21)(22)(23)(24) in absolute ethanol and then freshly redistilled diethylmalonic ester was added in a 1 : 1 molar ratio. After shaking the mixture overnight at room temperature, the alcohol was removed under vacuum and the white salt dried at room temperature (yield 87% on a 0.05 mol scale).…”
Section: Kinetic Measurementssupporting
confidence: 79%
“…That both the formation and decomposition reactions should have negative entropies of activation would not have been predicted, since the latter would be expected to be much more positive, within the experimental error. However, negative entropies have been observed for other reactions (14,18 that the incipient chloride ion enhances the acid, the negative entropies are again consistent solvation of the transition state of the decom-with many reports in the literature (19)(20)(21)(22)(23)(24) in absolute ethanol and then freshly redistilled diethylmalonic ester was added in a 1 : 1 molar ratio. After shaking the mixture overnight at room temperature, the alcohol was removed under vacuum and the white salt dried at room temperature (yield 87% on a 0.05 mol scale).…”
Section: Kinetic Measurementssupporting
confidence: 79%
“…Positive values for this quantity are commonly observed and partially cancel the enthalpy difference giving a small isotope effect. Negative values, while unusual, have been reported on several occasions (8,9,12,13) and cnliance the rate ratio. However, the activation parameters quoted by McLennan and Wong (10) are based on rate constant measurements at only two different temperatures, so the uncertainties may be large.…”
Section: Introductionmentioning
confidence: 79%
“…compound reacts via an E2 mechanism. The small isotope effect of 2.8 shows that the transition state structure is unsvminetrical and there is no doubt, from the observation that di-(p-11itrophenyl)methane readily yields a carbanion oil treatment with alkoxides in alcohol (8,9), that the extent of C-H bond rupture must be considerably greater than that of C-F bond rupture. Thus, the mechanism is E2, with a carbanion-like transition state.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies of the proton-transfer reactions of nitroalkanes with both neutral and anionic bases have been carried out over the past half-century. The reactions are conveniently studied by spectrophotometry since the stable anionic products exhibit strong absorbance bands in the visible spectral region. The very large deuterium kinetic isotope effects (≅50) reported by Caldin and Mateo 7,8 for the reaction between 4-nitrophenylnitromethane (NPNM) with tetramethylguanidine (TMG), a strong organic base with an exchangeable N−H, in toluene were quickly challenged by two groups. ,, Reinvestigations of the reaction revealed that the results reported for the D-labeled acid are unreliable due to proton/deuteron (H/D) exchange and that KIE app was lowered to about 11 when the base was changed to (Me 2 N) 2 CND.…”
mentioning
confidence: 99%